Freedom of speech in the structure of the legal status of an individual. (Journal of actual problems of jurisprudence, 2016)
This article considers questions of a freedom of speech and legal status of the personality and their interrelation. At the same time investigated legal status of personality. An author in this article investigates rights and individual freedoms according to categories. An author on the basis of analysis examines freedom of speech.
Keywords: a man and a citizen; human rights; political rights; personal rights; the right to freedom of speech; freedom of access to information